Diseño e implementacion de un sistema de inventarios para mejorar la Administracion del Comercial David & David del Cantón Montalvo, Provincia los Rios, año 2012 - Viejó Lozano, Evelyn Johanna (2012)
In the commercial DAVID & DAVID, dedicated to the purchase - sale of hardware products and building society in general, presents major flaws in how perform an inventory system successful that decreases the problems that arise daily. For this reason we have been in need of a research study in this institution to determine what inventory system can contribute with the completion of the problematic of the commercial. Through research, analysis and information gathering through interviews and surveys to the authorities and employees, as well as the scientific theory obtained from books, Web pages. With the information obtained was carried out the preliminary design according to requirements and steps set out in the manual of graduation of the faculty, it was presented to the Honorable University Council for their respective approval. The sample chosen was the total of the universe resulting 17 person surveyed and interviews was carried out to the owner manager, Sub 2 employees, according to the tabulation, analysis and interpretation of results, and Manager was raised the following hypothesis: "The implementation of an inventory system, will allow improving the administration of the commercial 'DAVID & DAVID' in the year 2012". Also by analyzing the results obtained we can say that most employees say that the need to implement a system of inventories is of vital importance for the good development of the commercial. I recommend that employees must commit to work activities of the commercial and mostly contributing to improvement of the system of inventories. Finally I recommend the implementation of a system of inventories that will improve the management of the commercial.